A Comparative Evaluation of Closed and Open Treatment in the Management of Unilateral Displaced Mandibular Subcondylar Fractures: A Prospective Randomized Study. Issue 3 (September 2018) - Singh, Virendra; Kumar, Neeraj; Bhagol, Amrish; Jajodia, Neha
The aim of the study is to evaluate closed and open treatment in the management of unilateral displaced mandibular subcondylar fractures. Twenty patients with unilateral subcondylar fractures of the mandible were evaluated with degree of displacement of more than 20 degrees and ramal height shortening of more than 10 mm. They were informed of the need for 6-month follow-up. Patients were thoroughly informed, explaining the possible advantages and disadvantages of the open and closed treatment options. Radiographic parameters included the level of fracture, deviation of fragment, and ramal height shortening. Correct anatomical reduction is achieved by open treatment as compared with closed treatment. Regarding pain, mouth opening, and lateral excursion movement, statistically significant difference was found in both groups ( p < 0.01). In radiographic assessment of ramal height shortening and fracture displacement, statistically significant difference was found ( p < 0.01). And no significant complication is found in both treatment groups. The results of this study favor the open treatment for the management of displaced subcondylar fractures. However, the treatment results are also acceptable for closed group.